Phytolith evidence of cereal processing in the Danube Delta during the Chalcolithic period. (10th February 2019) - Danu, Mihaela; Messager, Erwan; Carozza, Jean-Michel; Carozza, Laurent; Bouby, Laurent; Philibert, Sylvie; Anderson, Patricia; Burens, Albane; Micu, Cristian
Abstract: Recent excavations at Taraschina, south-eastern Romania, have revealed an extensive Chalcolithic settlement in the heart of the Danube Delta. Based on ceramic data, Taraschina was attributed to the Gumelniţa Culture and dated to the mid 5th millennium BC by radiocarbon dating. Phytolith analysis was conducted at Taraschina in order to reconstruct some activities carried out by the Chalcolithic populations in the Danube Delta. The study was undertaken on the site sediments, as well as on additional deposits sampled around the site by coring. The results show that phytoliths characterizing cereal processing are attested in archaeological deposits, as well as in the surrounding sequence. Our study highlights an important signal of cereal processing in the heart of the Danube Delta, 6000 years ago.